Changes in soil bacterial communities after contamination with hexadecane - Pucci, Graciela N. (2012)
This paper reports on changes in the soil bacterial community from a petroleum zone of Argentina. Changes were observed in a microcosm test which was subject to contamination with hexadecane. The determination of hydrocarbons and bacterial counts were performed weekly. Changes in bacterial diversity were determined by the analysis of membrane fatty acids (FAMEs), identified and quantified by gas chromatography using according to MIDI parameters. It was observed that contamination with hexadecane cause a disturbance in the soil leading to a change in the bacterial community structure.